Clinicians' Perspectives on Racism and Black Women's Maternal Health - Brittany D. Chambers; Brianne Taylor; Tamara Nelson; Jessica Harrison; Arielle Bell; Allison O'Leary; Helen A. Arega; Sepehr Hashemi; Safyer McKenzie-Sampson; Karen A. Scott; Tina Raine-Bennett; Andrea V. Jackson; et al. (Mary Ann Liebert, 2022)
Objective: The objective of this study was to explore clinician perceptions of how racism affects Black women's pregnancy experiences, perinatal care, and birth outcomes. Materials and Methods: We conducted 25 semi-structured interviews with perinatal care clinicians practicing in the San Francisco Bay Area (January to March 2019) who serve racially diverse women. Participants were primarily recruited through ?Dear Perinatal Care Provider? email correspondences sent through department listservs. Culturally concordant, qualitatively trained research assistants conducted all interviews in person. The interviews ranged from 30 to 60 minutes and were audio-recorded and professionally transcribed verbatim. We used the constant comparative method consistent with grounded theory to analyze data. Results: Most participants were obstetrician/gynecologists (n?=?11, 44%) or certified nurse midwives (n?=?8, 32%), had worked in their current role for 1 to 5 years (n?=?10, 40%), and identified as white (n?=?16, 64%). Three themes emerged from the interviews: provision of inequitable care (e.g., I had a woman who had a massive complication during her labor course and felt like she wasn't being treated seriously); surveillance of Black women and families (e.g., A urine tox screen on the Black baby even though it was not indicated, and they didn't do it on the white baby when, in fact, it was indicated); and structural care issues (e.g., the history of medical racial experimentation). Conclusion: Clinicians' views about how racism is currently operating and negatively impacting Black women's care experiences, health outcomes, and well-being in medical institutions will be used to develop a racial equity training for perinatal care clinicians in collaboration with Black women and clinicians.